Culture, Rhetoric, and Voting : The Presidential Election of 2012 - Pauly, Robert J., 1967-; Covarrubias, Jack; Lansford, Tom; Brattebo, Douglas M. (Book collections on Project MUSE., 2016)
"The presidential election of 2012 was among the most important in American history, both for the policies that will persist due to its result as well as the national political transformation it portends. The contest's outcome was the product of complex and fast-moving societal changes--demographic, technological, and economic--surfacing in American society. This volume, consisting of writings by leading scholars of American politics and the American presidency, examines the 2012 presidential election in its many facets. Particularly prominent in these analyses are: psychology, religion, and culture, rhetoric, and voting"--